Potency of Biocoagulant from Cationic Modified Starch of Balbis Banana Blossom Waste for Palm Oil Wastewater Treatment: Literature Study - Fadhallah, Esa Ghanim; Hidayat, Alif Fikri Nur; Saffanah, Arfika Julya; Iswahyudi, Bella Amanda; Wasalamah, Diah Shihatin; Putri, Eka Cahyani; Ningtias, Nadila; Ummi, Yana Hijriyatin (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2023)
Lampung is one of the provinces producing Indonesia's second-largest banana crop. Operational activities at the Palm Oil Mill produce a by-product of Palm Oil Mill Effluent (POME), which can potentially be the most enormous environmental pollution. Communities often use chemicals to treat liquid waste, which causes health problems, cannot be decomposed, and can damage the environment. Therefore, treating liquid waste using organic materials that are more environmentally friendly, safe for health and easily degraded is necessary. By modifying cationic starch, natural polymers found in banana blossom waste may be utilized for producing natural biocoagulant that are more effective. This paper aims to review the potential of cationic-modified balbis banana blossom waste starch as a natural biocoagulant for processing palm oil waste. Starch was first modified into cationic starch by etherification method with the help of HMMAHC cationic reagents. The mechanism of cationic starch as a biocoagulant is the exchange of starch cation ions and waste anions to form bridges between colloidal particles and then form flocs that can precipitate. The implementation technique of this idea is by collaborating with several parties to ensure the successful use of banana hump starch as a biocoagulant material, providing support and facilities for the industry and promoting the use of biocoagulant, conducting literature studies related to the use of banana hump starch as a natural biocoagulant, testing the effectiveness of biocoagulant, implemented in the palm oil processing industry.